Utilization of Artificial Intelligence (AI) for Evaluating Students' Arabic Speaking Skills - Latifatul Mahbubah (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2026)
Evaluation of speaking skills (Maharah al-Kalam) in Arabic language learning often faces challenges related to objectivity, lecturer time constraints, and a lack of practice opportunities for students. This study aims to explore the use of Artificial Intelligence (AI) technology as an automated evaluation tool capable of providing real-time feedback. This research used a descriptive qualitative research method, using observation and documentation as data collection techniques and in the data analysis process using several stages, namely data collection, data reduction, data verification, data presentation and drawing conclusions. The results of the study indicate that the use of AI in evaluating students' speaking skills produces two forms: evaluation with qualitative data results and evaluation with quantitative data results. Evaluations conducted with qualitative data results provide a clear description of the errors in the texts. The evaluations conducted with quantitative data results provide a percentage of students' success levels in the kalam, and these results become a reference for evaluations conducted in subsequent meetings.